2019
DOI: 10.15420/aer.2019.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardiac Electronic Devices in the Elderly Population

Abstract: The use of cardiac implantable electronic devices in the management of patients with heart rhythm conditions is well established. As the population ages, the use of cardiac implantable electronic devices in the elderly is likely to increase. This review provides a summary of the indications, implantation considerations and pragmatic advice on how to approach the use of these devices in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
(41 reference statements)
0
15
0
4
Order By: Relevance
“…On the other hand, patients' co-morbidities play a significant role in cardiac device implantation. For instance, patients with moderate to severe renal impairment and a history of life-threatening ventricular arrhythmias did not show benefits from ICD implantation [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients' co-morbidities play a significant role in cardiac device implantation. For instance, patients with moderate to severe renal impairment and a history of life-threatening ventricular arrhythmias did not show benefits from ICD implantation [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chest pain during the procedure: A moderate sedation is given during CIED implantation because patients undergoing such procedures are usually elderly and have multiple comorbid conditions. 7 This limits the use of proper analgesia and sedation to limit the adverse effects of sedatives and anaesthetics and imparts an important role of local anaesthesia for pain control. If local anaesthesia is not given adequately, patients might experience pain during different steps of device implantation.…”
Section: Evaluation Of Chest Pain After Cied Implantationmentioning
confidence: 99%
“…Most of the physicians at our institute use a sub clavicular approach for subclavian vein access but one of our study has shown the supra-clavicular approach to be noninferior and time-efficient in temporary transvenous pacing. 9 Hence, we prefer a supraclavicular approach in CIED surgeries as well.…”
Section: Evaluation Of Chest Pain After Cied Implantationmentioning
confidence: 99%
“…1 The prevalence of CIED patients is likely to rise considerably with the aging population. [1][2][3] Because CIED patients have underlying structural heart disease, they often require complex downstream clinical decisions, thereby warranting noninvasive imaging. As a versatile modality, cardiovascular magnetic resonance (CMR) is wellsuited for a comprehensive assessment including cardiac function, structure, perfusion, hemodynamics, and viability.…”
Section: Introductionmentioning
confidence: 99%
“…Over 3 million patients in the United States are implanted with a cardiac‐implanted electronic device (CIED) such as implantable cardioverter‐defibrillators (ICDs), pacemaker, or cardiac resynchronization therapy (CRT) for increasing their lifespan and/or quality of life 1 . The prevalence of CIED patients is likely to rise considerably with the aging population 1‐3 . Because CIED patients have underlying structural heart disease, they often require complex downstream clinical decisions, thereby warranting noninvasive imaging.…”
Section: Introductionmentioning
confidence: 99%